General and special education inclusion in an age of change impact on students with disabilities - Bakken, Jeffrey P.; Obiakor, Festus E. (Bingley, U.K. : Emerald, 2016)
This volume addresses general and special education inclusion and how the education field has changed over time. The topic of inclusion has transformed over the years from when it was first introduced and as a result of legislation, new trends, and current research investigations. In addition, this topic can be somewhat controversial depending on the disability the child might have or those professionals involved in the process of instructing individuals with disabilities. Currently, there is no comprehensive resource that effectively covers these advances with the breath of topics as this volume. This volume will address the most current perspectives and issues related to general and special education inclusion and will be written by leaders in the field with particular expertise in this area. This volume will be an excellent resource for special educators, administrators, mental health clinicians, school counsellors, and psychologists. The layout of the volume will allow readers to follow general and special education inclusion in a very logical and thoughtful process from students with high incidence disabilities to those with low incidence disabilities.
General and special education in an age of change: an introduction / Jeffrey P. Bakken -- Inclusion and students with learning disabilities / Mary Cece Young, Carrie Anna Courtad -- Fape accompli: misapplication of the principles of inclusion and students with EBD / Frederick J. Brigham, Soo Y. Ahn, Ashley N. Stride, John William McKenna -- Inclusion and students with an intellectual disability / Emily C. Bouck, Jiyoon Park -- Inclusion of deaf/hard of hearing students in the general education classroom / Christy M. Borders, Stephanie Gardiner-Walsh, Molly Herman, Molly Turner -- Inclusion and students with visual impairments / Stacy M. Kelly -- Inclusion of students with autism spectrum disorders / Stacey Jones Bock, Christy M. Borders, Kristi M. Probst -- Including students with extensive and pervasive support needs / Michael L. Wehmeyer, Karrie A. Shogren, Jennifer A. Kurth, Mary E. Morningstar, Elizabeth B. Kozleski, Martin Agran, Lewis Jackson, J. Matt Jameson, John McDonnell, Diane L. Ryndak -- Inclusion and students with traumatic brain injuries / Angela L. Canto, Megan A. Crisp, Helaine Larach, A. Paige Blankenship -- Inclusion and students with communication impairments / Lindsay Bondurant -- Inclusion of students with physical disabilities and other health impairments / Eugene F. Asola, Festus E. Obiakor.
Includes bibliographical references.
Print version record
Keywords: Education -- General; Education; Inclusive education; Special education; Students with disabilities